Number of blood pressure measurements needed to estimate long-term visit-to-visit systolic blood pressure variability for predicting cardiovascular risk: a 10-year retrospective cohort study in a primary care clinic in Malaysia - Lim, Hooi Min; Chia, Yook Chin; Ching, Siew Mooi; Chinna, Karuthan (BMJ Publishing Group, 2019)
Objective: To determine the reproducibility of visit-to-visit blood pressure variability (BPV) in clinical practice. We also determined the minimum number of blood pressure (BP) measurements needed to estimate long-term visit-to-visit BPV for predicting 10-year cardiovascular (CV) risk. Design: Retrospective study Setting: A primary care clinic in a university hospital in Malaysia. Participants: Random sampling of 1403 patients aged 30 years and above without any CV event at baseline. Outcomes measures: The effect of the number of BP measurement for calculation of long-term visit-to-visit BPV in predicting 10-year CV risk. CV events were defined as fatal and non-fatal coronary heart disease, fatal and non-fatal stroke, heart failure and peripheral vascular disease. Results: The mean 10-year SD of systolic blood pressure (SBP) for this cohort was 13.8±3.5 mm Hg. The intraclass correlation coefficient (ICC) for the SD of SBP based on the first eight and second eight measurements was 0.38 (p<0.001). In a primary care setting, visit-to-visit BPV (SD of SBP calculated from 20 BP measurements) was significantly associated with CV events (adjusted OR 1.07, 95% CI 1.02 to 1.13, p=0.009). Using SD of SBP from 20 measurement as reference, SD of SBP from 6 measurements (median time 1.75 years) has high reliability (ICC 0.74, p<0.001), with a mean difference of 0.6 mm Hg. Hence, a minimum of six BP measurements is needed for reliably estimating intraindividual BPV for CV outcome prediction. Conclusion: Long-term visit-to-visit BPV is reproducible in clinical practice. We suggest a minimum of six BP measurements for calculation of intraindividual visit-to-visit BPV. The number and duration of BP readings to derive BPV should be taken into consideration in predicting long-term CV risk.